Bootleg : murder, moonshine, and the lawless years of prohibition - Blumenthal, Karen (RB Flash Point, 2011)
Chronicles the history of Prohibition in the United States, a period from 1920 to 1933 during which it was illegal to sell or drink alcohol, discussing how what began as a movement to heal social ills, became a burden to ordinary citizens and a boon to criminals.